Revision of the elegans-group of Alona s. lato and its status as a subgenus of Coronatella Dybowski & Grochowski, 1894 (Cladocera: Anomopoda: Chydoridae) - Sinev, Artem Y. (Zootaxa, 2020)
The taxonomic status of the elegans-group of Alona s. lato (Cladocera: Anomopoda: Chydoridae) is herein examined. The West Palearctic Alona elegans Kurz, 1875 and poorly known African taxon Coronatella cf. bukobensis (Weltner, 1897) are redescribed, and new data on morphology of Coronatella circumfimbriata (Megard, 1967) and Coronatella rectangula (Sars, 1861) is added. Based on analysis of original and literature data, the elegans-group is herein suggested as a separate subgenus within the genus Coronatella, namely Coronatella (Ephemeralona) subgen. nov. Main diagnostic features of the latter include: (1) seta arising from the basal segment of antenna endopodite much longer than endopodite; (2) acessory seta of limb I long, almost as long as ODL seta; (3) setae 2-3 of IDL armed with uniform thin setulae; (4) exopodite of limb II with a very short, rudimentary seta. Coronatella (Ephemeralona) subgen. nov. is a morphologically uniform basal group of the genus. It is distributed mostly in the arid belt of the Old World, with a single species known from South Africa. C. (Coronatella) is distributed worldwide; it is composed of several distinct species-groups with overlapping areas of distribution. A checklist of Coronatella species is provided.